2022
DOI: 10.26740/jekobi.v5n1.p54-66
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Literasi Zakat dan Kepercayaan terhadap Minat Membayar Zakat Melalui Zakat Digital pada Masyarakat di Kabupaten Sidoarjo

Abstract: Di era digital pengumpulan dana zakat dapat dilakukan melalui platform digital yang dimiliki oleh lembaga amil zakat. Namun adanya kemudahan tersebut, memiliki resiko yang dapat mempengaruhi minat masyarakat Kabupaten Sidoarjo untuk membayarkan zakatnya melalui zakat digital. Penelitian ini bertujuan untuk mengetahui pengaruh literasi zakat dan kepercayaan terhadap minat membayar zakat melalui zakat digital pada masyarakat di Kabupaten Sidoarjo. Pada penelitian ini menggunakan metode kuantitatif  menggunakan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…The study concluded that financial technology based on good digital literacy would increase interest in paying ZIS by Muzaki. Contrary to this research, Febiana et al (2022) and Anggraini and Indrarini (2022) concluded that literacy only affects one's interest in paying ZIS digitally.…”
Section: E-commercecontrasting
confidence: 64%
“…The study concluded that financial technology based on good digital literacy would increase interest in paying ZIS by Muzaki. Contrary to this research, Febiana et al (2022) and Anggraini and Indrarini (2022) concluded that literacy only affects one's interest in paying ZIS digitally.…”
Section: E-commercecontrasting
confidence: 64%
“…The perceptions of ease of use, usefulness, and trust have a significant role in shaping the attitudes and behaviors of Muzakki individuals who express a desire to use digital platforms for making zakat donations. Another factor that influences Muzakki's trust is the security (Anggraini & Indrarini, 2022).…”
Section: Introductionmentioning
confidence: 99%